A Comparative Study of Surgical Correction of Idiopathic Scoliosis With Spinal Transpedicular Metal Structures in Children - Nadirov, Nurbek; Vissarianov, Sergey (Frontiers in Pediatrics, 2022)
A comparative study of surgical correction of idiopathic thoracic scoliosis using transpedicular spinal systems in children was performed. The study showed that using the transpedicular supporting elements along the entire length of the deformation (concave and convex sides) using the VCM (vertebral column manipulation) system, the correction was significantly better (p≤0.05) than for the patients for whom the screws were not installed over two or more vertebrae from the concave side of the curvature, regardless of the magnitude of the spinal deformity. The kyphosis and lordosis were completely restored to their physiological values in all groups of patients.